Fracture resistance of aluminum alloys notch toughness, tear resistance, and fracture toughness - Kaufman, J. G. 1931- (Aluminum Association ; ASM International, 2001)
Annotation Kaufman prevents this summary of data on the fracture characteristics of aluminum alloys, broadly based on a publication by Alcoa in 1964, Fracture Characteristics of Aluminum Alloys. Coverage includes tensile properties as indicators of fracture behavior; notched-bar impact and related tests for toughness; notch toughness and sensitivity; tear resistance; fracture toughness; the interrelation of fracture characteristics; toughness at subzero and elevated temperatures; subcritical crack growth; and metallurgical considerations in fracture resistance. Most of the data is presented in only the English/engineering units, contrary to normal ASM International and Aluminum Association, Inc. policies. The author's credentials are not stated. c. Book News Inc